2013
DOI: 10.1007/s00223-013-9736-4
|View full text |Cite
|
Sign up to set email alerts
|

Dosage Effect of a Phex Mutation in a Murine Model of X-Linked Hypophosphatemia

Abstract: X-linked hypophosphatemia (XLH) is caused by mutations in the PHEX gene, which increase circulating levels of the phosphaturic hormone, fibroblast growth factor 23 (FGF23). Since XLH is a dominant disease, one mutant allele is sufficient for manifestation of the disease. However, dosage effect of a PHEX mutation in XLH is not completely understood. To examine the effect of Phex genotypes, we compared serum biochemistries and skeletal measures between all five possible genotypes of a new murine model of XLH (Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Accordingly, these mothers with the pA defect did not always manifest even this biochemical hallmark of renal Pi wasting in XLH. Therefore, the pA mutation seems to manifest a gene dosage effect, including on biochemical parameters of Pi homeostasis, that may be unusual for other PHEX mutations as reported in 2013 by Ichikawa et al (28) Studies of large kindreds with the c. Ã 231A > G defect should clarify its gender effects.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, these mothers with the pA defect did not always manifest even this biochemical hallmark of renal Pi wasting in XLH. Therefore, the pA mutation seems to manifest a gene dosage effect, including on biochemical parameters of Pi homeostasis, that may be unusual for other PHEX mutations as reported in 2013 by Ichikawa et al (28) Studies of large kindreds with the c. Ã 231A > G defect should clarify its gender effects.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, in the presence of only a slightly improved serum phosphate concentration, the double mutant mice markedly up-regulated FGF23 mRNA, well above the Hyp mouse with WT GALNT3 alleles (>20 fold in 12 week old Hyp mice) (55). In contrast to patients with ADHR, XLH patients and controls showed similar correlations between serum iron and iFGF23/cFGF23 (albeit XLH was on an increased scale) supporting that iron responsiveness is likely not a central factor in the pathogenesis of XLH (51). These results indicate that the PHEX mutation, in addition to potentially resulting in altered osteocyte cell differentiation, alters biological sensing for phosphate.…”
Section: Fgf23 and Iron Metabolismmentioning
confidence: 84%
“…Inactivating PHEX mutations have previously been associated with a differentiation defect in osteocytes in the Hyp mouse model of XLH (47) which appears to be similar to that found in the Dmp1 -null mouse (see ARHR-1), and Hyp bone FGF23 mRNA expression is elevated (Figure 1) (48,49). The increased FGF23 mRNA levels indicate that the increase in serum FGF23 in XLH is due to both over production by skeletal cells, as well as potentially a decrease in secondary iFGF23 proteolysis by SPC family members (50,51). The interactions between FGF23 and PHEX are indirect as FGF23 is not a PHEX substrate (52).…”
Section: Fgf23 and Iron Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Dosage effects of the PHEX gene were also examined by comparing heterozygous and homozygous female Hyp mice. It was demonstrated that the skeletal phenotype was worse in homozygous female Hyp mice, but both groups of mice had comparable serum FGF23 levels (Ichikawa, Gray, Bikorimana, & Econs, 2013).…”
Section: Fgf23-mediated Disordersmentioning
confidence: 98%